2020
DOI: 10.30773/pi.2019.0258
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Patients or Conventional Lecture for Teaching Communication Skills to Undergraduate Medical Students: A Randomized Controlled Study

Abstract: Objective The conduct of a medical interview is a challenging skill, even for the most qualified physicians. Since a training is needed to acquire the necessary skills to conduct an interview with a patient, we compared role-play with standardized patients (SP) training and a conventional lecture for the acquisition of communications skills in undergraduate medical students.Methods An entire promotion of third year undergraduate medical students, who never received any lessons about communications skills, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Including an Objective Structured Clinical Examination and seeking SP feedback are also considered crucial. 9,35,[39][40][41][42][43][44][45] To achieve improvements in medical students' communication skills and, potentially, their eventual medical performance, both features should be incorporated in the CST. 1,7 Furthermore, the identification of the long-term outcomes-such as sustained communication-skills improvement and overall clinical proficiency-should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Including an Objective Structured Clinical Examination and seeking SP feedback are also considered crucial. 9,35,[39][40][41][42][43][44][45] To achieve improvements in medical students' communication skills and, potentially, their eventual medical performance, both features should be incorporated in the CST. 1,7 Furthermore, the identification of the long-term outcomes-such as sustained communication-skills improvement and overall clinical proficiency-should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…As in several previous investigations, simulated patients were portrayed by mental health professionals [ 34 , 58 , 59 , 61 , 71 , 74 ]. Simulated patients were trained to portray the simulated patient by two academic teachers (PR & MR), themselves trained as health simulation trainer in a short (one-week) university course.…”
Section: Methodsmentioning
confidence: 99%
“…SPs are mainly used as a tool for evaluating students. However, since there is immense learning potential for students in working with SPs as a teaching resource, the method has the potential to be effective in clarify missing items, showed more encouragement of the patient's emotions, and were better at managing the time and performance of the interview [31]. However, in the study by Geoffroy and colleagues, the students were observed during an interview and no challenging behaviours were targeted.…”
Section: Suggestions For Changementioning
confidence: 99%
“…However, as concluded in a recent systematic review, there is very little published work assessing the impact of SP use in medical educations and also evaluating any behaviour change in the participants [30]. Although a few studies have included CS outcomes in students being trained in taking a medical history [31] or breaking bad news to a SP [32,33], indicating some positive effects, studies seldom include a wider range of challenging behaviours or explore both feasibility and behavioural effects.…”
Section: Introductionmentioning
confidence: 99%